INDUSTRI HALAL DARI PERSPEKTIF POTENSI DAN PERKEMBANGANNYA DI INDONESIA - Herianti, Herianti; Siradjuddin, Siradjuddin; Efendi, Ahmad (Indonesia Journal of Halal, 2023)
With more than 200 million people who are Muslim, Indonesia is one of the main markets for producers of halal products. The halal product business is very promising in our country, so this article will examine the position of the Indonesian halal industry in its development. In particular, this research focuses on the government's role in exploring the potential and development of the halal industry in Indonesia. This article uses a literature review or literature study before conducting a descriptive analysis of the solutions and results. Then from the search results from various related journals, books and several reports related to the topic of discussion, the result is that there is a lot of room for growth in the halal industry, which has experienced very rapid development in recent years, especially in the field of halal food and beverages. , halal clothing, halal tourism, and halal finance. The government has also supported other potential sectors, such as halal medicines, media and the environment. Overall, the current development and halal industry has enormous potential to improve the country's economy. However, even though there is great potential, there are many challenges to be faced, such as a lack of public awareness about halal and a low level of halal literacy. So, this article can be part of increasing public knowledge about halal and then being part of the development of the halal industry in Indonesia.